2004
DOI: 10.4049/jimmunol.173.6.3773
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and Function of CD8+ T Cells Expressing Ly49 Inhibitory Receptors Specific for MHC Class I Molecules

Abstract: MHC class I-specific Ly49 inhibitory receptors regulate NK cell activation, thereby preventing autologous damage to normal cells. Ly49 receptors are also expressed on a subset of CD8+ T cells whose origin and function remain unknown. We report here that, despite their phenotypic and cytolytic similarities, Ly49+CD8+ T cells and conventional Ly49−CD44high memory-phenotype CD8+ T cells present strikingly distinct features. First, under steady state conditions Ly49+CD8+ T cells are poor cytokine producers (TNF-α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 60 publications
5
25
0
Order By: Relevance
“…In this respect, chronic antigenic exposure has been shown to induce MHC-NKR expression on mouse CD8 T cells [6]. It is thus tempting to speculate that the chronic CMV infection, which persisted for 20 months in this patient, led to MHC-NKR expression on the cd T cells involved in the antiviral immune response.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In this respect, chronic antigenic exposure has been shown to induce MHC-NKR expression on mouse CD8 T cells [6]. It is thus tempting to speculate that the chronic CMV infection, which persisted for 20 months in this patient, led to MHC-NKR expression on the cd T cells involved in the antiviral immune response.…”
Section: Discussionmentioning
confidence: 82%
“…In mice, expansion of self-reactive CD8 + T cells expressing an inhibitory MHC-NKR Ly49 was obtained upon persistent challenge with a self antigen [6]. Altogether, these observations suggest that MHC-NKR expression is acquired after antigenic stimulation and is associated with expansion and survival of T cells.…”
Section: Introductionmentioning
confidence: 82%
“…The only reported mechanism of inducing Ly49 receptor expression on T cells, which had defined ligand specificity, used a model of chronic T cell stimulation. In this model, female CD8 + T cells, which express transgenic TCR recognizing the male HY antigen, up-regulate Ly49 expression when transferred to male Rag-deficient recipients, but this only occurs if HY-specific CD4 T cells are co-transferred [27]. One further piece of evidence for an activation-induced NK programming by mouse cd T cells is seen in the skewing of the TCR repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…At the immature DX5 -stage, NK cells express multiple NK receptors including CD94/NKG2, NKG2D and NKp46, but are unable to perform granule-mediated cytotoxicity [21][22][23]. During maturation to DX5 + mature cells, NK cells start to express Ly49 MHC class I receptors [22][23][24], and undergo an education process during which NK cells expressing inhibitory receptors that recognize self MHC class I are "licensed" to perform more potent effector functions [25][26][27][28].cd T cells, like ab T cells, develop in the thymus, where V(D)J recombination of TCR genes occurs. Using T cell receptor d locus-histone 2B-enhanced GFP (Tcrd-H2BEGFP) knock-in mice in which an IRES-controlled H2B-EGFP fusion protein is present in the 3 0 untranslated region of the Tcrd constant gene [29], we have recently shown that developing cd T cells undergo a "TCR quality control checkpoint" upon successful expression of TCRcd.…”
mentioning
confidence: 99%
“…ϩ T cells that express other NKRs (Ly49 or killer immunoglobulinlike receptors), display reduced frequencies of IFN-␥ and TNF-␣ expression compared with NKR Ϫ CD8 ϩ T cells [43,44], whereas Kambayashi et al reported that murine influenza-specific NKR ϩ T cells produce IFN-␥ in response to influenza antigens [45].…”
Section: Cd56mentioning
confidence: 99%